Acetylcholinesterase(AChE)-catalyzed hydrolysis of long-chain thiocholine esters: Shift to a new chemical mechanism - Jung, DI; Shin, YJ; Lee, ES; Moon, T; Yoon, CN; Lee, BH (KOREAN CHEMICAL SOC, 2003)
The kinetic and chemical mechanisms of AChE-catalyzed hydrolysis of short-chain thiocholine esters are relatively well documented. Up to propanoylthiocholine (PrTCh) the chemical mechanism is general acid-base catalysis by the active site catalytic triad. The chemical mechanism for the enzyme-catalyzed butyrylthio- choline(BuTCh) hydrolysis shifts to a parallel mechanism in which general base catalysis by E199 of direct water attack to the carbonyl carbon of the substrate. [Selwood, T., et al. J. Am. Chem. Soc. 1993, 115, 1047710482] The long chain thiocholine esters such as hexanoylthiocholine (HexTCh), heptanoylthiocholine (HepTCh), and octanoylthiocholine (OcTCh) are hydrolyzed by electric eel acetylcholinesterase (AChE). The kinetic parameters are determined to show that these compounds have a lower Michaelis constant than BuTCh and the pH-rate profile showed that the mechanism is similar to that of BuTCh hydrolysis. The solvent isotope effect and proton inventory of AChE-catalyzed hydrolysis of HexTCh showed that one proton transfer is involved in the transition state of the acylation stage. The relationship between the dipole moment and the Michaelis constant of the long chain thiocholine esters showed that the dipole moment is the most important factor for the binding of a substrate to the enzyme active site.
Keywords: ALZHEIMERS-DISEASE; CHOLINE ESTERS; INHIBITORS; BINDING; BRAIN; GORGE